The experience of migrants from Central and Eastern European state members: The case of the UK in the context of EU enlargement - Velkov, Damyan (2008)
The Eastern enlargement of the EU and accession of the Central and Eastern European countries brought significant consequences for the new and existing members of the Union and contributed to the change of economic climate in those countries. Following the fact that prior to accession in May 2004 the UK was one of the three countries that fully opened up their labour market to the citizens of the new member states, it resulted in intense migration from the members of the A-8 countries to the UK. The aim of this dissertation is to uncover the experience of the migrants from the A-10 countries in the UK and analyse how the social climate and government regulations affected their life as well as the opportunities for them in the UK.